An Analytical Study of the Impact of Military Spending on the Chinese Economy Growth for the Period (1990-2018) - najem, Rafah Adnan; najem, Rafah Adnan; Khalaf, Fatma Ebrahem; Ebrahem, Anwar saeed (Journal of Economics and Administrative Sciences, 2021)
The increase in military spending has become a feature of the times for many countries, including China. They have sought to increase their defence spending, not with the aim of domination and possession, but rather to protect their economic interests and to secure their foreign trade. The research aims to identify the impact of military spending by studying the nature of defence spending and its role in providing security. And stability and facilitating foreign investment in it, as well as storming the military industry, securing some humanitarian supplies, and participating in a variety of public works that can be used in the civil and military fields, and the aim of the research is to identify the impact of military spending on achieving Chinese economic growth. The research problem is: Is the increase in military spending The Chinese influence increases economic growth rates or not, while the research assumes that defence programs work to provide political stability and develop defence methods. The research adopted the descriptive and analytical approach in the first and second researches, while the third topic was strengthened by the standard aspect in order to achieve its goals and prove its hypotheses according to tests. Several of them are: unit root (stability test), Vector Auto Regression and Granger Causality based on World Bank data for research variables for the sample country (China) for the years (1990-2018), and the research found a strong positive moral relationship between military spending and economic growth and trade exchange and an inverse moral relationship with unemployment rates, and the research concluded that there is a bilateral causal relationship. The trend between military spending and economic growth, as well as the participation of economic growth and military spending in increasing the volume of exports and thus improving trade exchange for the benefit of the country